Urine Organic Acids as Metabolic Indicators for Global Developmental Delay/Intellectual Disability in Chinese Children - Chen, Baiyu; Zhan, Yalan; Kessi, Miriam; Chen, Shimeng; Xiong, Juan; Deng, Xiaolu; Yang, Lifen; Peng, Jing; Yin, Fei; He, Fang (Frontiers in Molecular Biosciences, 2021)
Objective: The purpose of this study was to search for differential metabolites in urine organic acids, and to characterize metabolic features that can be used to identify metabolites for exploration of global developmental delay (GDD)/intellectual disability (ID) etiology and pathogenesis. Methods: We screened positive test results that could explain GDD/ID from 1,253 cases, and the major differential metabolites in 132 urine organic acids from the 1,230 cases with negative results (863 GDD cases, 367 ID cases), and 100 typically developing children (TD). Non-supervisory principal component analysis and orthogonal partial least squares discriminant analysis were used to develop models to distinguish GDD/ID from TD children, and to detect major differential metabolites. Results: We get 23 positive results that could identify the cause of GDD/ID from 1253 cases diagnosed with GDD/ID. Among 1,230 negative results, we get the differential metabolites of the GDD group and the ID group had the same trend compared with the TD group. Twenty four differential metabolites were obtained from the GDD group, and 25 from the ID group (VIP>1.0, P<0.01). These differential metabolites were mainly related to the following pathways: the synthesis and degradation of ketone bodies, citrate cycle, alanine, aspartate and glutamate metabolism, pyrimidine metabolism, butanoate metabolism, pyruvate metabolism, fatty acid biosynthesis, valine, leucine and isoleucine degradation. Conclusions: The use of metabolomics research methods to detect urine organic acids of children with GDD/ID can discover differential metabolites, which might be valuable for future research on the etiology, pathogenesis, prognosis and possible interventions of GDD/ID. The significantly altered differential metabolites indicators could therefore be potential diagnostic biomarkers for GDD/ID.